تطور العلاقة السورية – التركية خلال الفترة (2000-2012) - علي, مدين; فارس, راما سليم (Latakia University Journal - Economic and Legal Sciences Series, 2014)
تهدف هذه الدراسة إلى بيان التغيرات في العلاقات السورية – التركية ،و نظرا" لما تتميز به هذه العلاقة من دقة وتطور مستمر في ملفاتها ، تم تقسيم الدراسة إلى مرحلتين : تغطي الأولى فترة التجاذب بين البلدين حتى العام 2011، أما الثانية : تتناول فترة الأزمة السورية التي دخلت فيها علاقتها مع تركيا مرحلة من التنافر والتوتر. وبالنتيجة نجد أن العلاقات بين البلدين شهدت تحسنا" مستمرا" في كافة الصعد في المرحلة الأولى نتيجة لإرادة قصدية من قبل الطرفين وصولا" إلى التعاون الاستراتيجي بينهما عام 2009 ، إلا أنه ومع حدوث الأزمة في سورية وجدت تركيا أن التغيير المحتمل في سورية قد يأتي بقوى حليفة لحزب العدالة والتنمية (الأخوان المسلمين) ، مايعني استرجاع المجال الاستراتيجي التركي القديم، مما أدى ومن ثم إلى توتر وتأزم علاقتها مع سورية، فقد أصبح لتركيا رغبة في الهيمنة والتدخل في شؤون سورية الداخلية حيث عمدت إلى فرض عقوبات اقتصادية على سورية طالت الوضع المعيشي للشعب السوري ، كما أنها تمادت وشاركت في عملية التدمير والنهب الممنهج للشركات والمؤسسات الصناعية السورية وبخاصة " في مدينة حلب . This study aimed to reveal changes in (Syrian- Turkish) relation ,though this relation is too sensitive, the study separated into two phases: -First: covers the rapprochement period between the two countries, till the year 2011. - Second: covers the Syrian crisis period when the two countries diverged. As a result, we see that Turkish –Syrian relations kept on developing in all fields in the first phase till the strategic cooperation in 2009 between them . but when the Syrian crisis happened, turkey found that the change which might happen in Syria could bring allies of The AKP (Muslim Brotherhood ),that means retake the old Turkish strategic domain , that cause stress and regress in the relation between Turkey and Syria, Turkey has started to plan to control and intervene in internal Syrian matters, it has been started by putting economic sanctions on Syria which had abad effect on the standard of living for Syrian inhabitants, then it started to go deeper in its intervention by planning to destroy Syrian industry and stealing industrial companies and factories ,especially in Aleppo.